Synergistic enhancement of glycogen production in Arthrospira platensis by optimization of light intensity and nitrate supply - Aikawa, Shimpei; Izumi, Yoshihiro; Matsuda, Fumio; Hasunuma, Tomohisa; Chang, Jo-Shu; Kondo, Akihiko (Bioresource technology, 2012)
Arthrospira (Spirulina) platensis, a fast-growing halophilic cyanobacterium able to accumulate glycogen, was investigated for its feasibility to serve as feedstock for fermentative production of biofuels and chemicals. The culture conditions most appropriate for glycogen production were identified. Glycogen production was maximized by the depleting nitrate source under a high light intensity of 700 μmol photons m(-2) s(-1). With optimal control of both light intensity and nitrate supply, glycogen production of A. platensis reached nearly 1.03 g L(-1) (a glycogen productivity of 0.29 g L(-1) d(-1)), which is, to the best of our knowledge, the highest α-polyglucan (glycogen or starch) production performance ever reported in microalgae. The outcome of this work supports A. platensis as a promising carbohydrate source for biorefinery.